2021
DOI: 10.37899/journallaedusci.v2i5.494
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges that English Teachers Face in the Employment of the Evaluation Matrix in Classes for Students with Learning Difficulties

Abstract: The current study aimed at identifying the challenges that English teachers face when they employ the evaluation Matrix in classes for students with learning difficulties. The study followed the descriptive-analytical method. A questionnaire was designed to meet the study objectives.  the study sample consisted of 136 English teachers of the primary education level in public schools in the city of Irbid.  The findings revealed that the challenges that English teachers face in employing the evaluation Matrix in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Even though previous studies have shown that there are advantages to teacher cooperation, there are also problems that need to be addressed. In addition, there is a lack of clarity on the particular characteristics that enable or inhibit successful teacher cooperation in PLCs and collaborative teaching methods (Alkhawaldeh & Khasawneh, 2022). This is a problem since several factors may have either of these effects.…”
Section: Problem Statementmentioning
confidence: 99%
“…Even though previous studies have shown that there are advantages to teacher cooperation, there are also problems that need to be addressed. In addition, there is a lack of clarity on the particular characteristics that enable or inhibit successful teacher cooperation in PLCs and collaborative teaching methods (Alkhawaldeh & Khasawneh, 2022). This is a problem since several factors may have either of these effects.…”
Section: Problem Statementmentioning
confidence: 99%
“…To provide an appropriate education for people with special needs, it is necessary to prepare an appropriate environment according to the type, degree, and needs of the disability. Poorly soundproofed, noisy, and dark areas are detrimental to the educational atmosphere (Alkhawaldeh & Khasawneh, 2022). As a result, while creating surroundings, people with special needs must be considered.…”
Section: Introductionmentioning
confidence: 99%